Advances on immunoregulation effect of astragalus polysaccharides - Wang, Xin-Yi; Wang, Rong-Can; Qu, Zheng-Yi; Zhu, Yan-Zhu; Li, Ya-Li (Frontiers in Natural Products, 2022)
Astragalus membranaceus (AM) is a traditional chinese medicine (TCM) with active substances such as saponins and polysaccharides, The most abundant active ingredient is astragalus polysaccharides (APS). It is a natural extract with multiple activities such as anti-viral, anti-tumor and the immune-enhancing effects. In recent years, studies on the role of APS in immunomodulatory direction have been increasing, and Numerous studies have shown that APS has a better immune enhancing effect. This paper outlines the immunomodulatory effects of APS in terms of immune cells, nonspecific immunity, anti-viral immunity, anti-tumor effects, and applications in animal production, which would provide a base for the further applications of APS. Herein, this current review intends to describe the immunomodulatory effects of APS with underlying mechanisms of therapeutic effects.